Phthalates exposure and pubertal development in a 15-year follow-up birth cohort study in Taiwan - Su, Pen-Hua; Huang, Jing-Yang; Wang, Shu-Li Julie; Chang, Hua-Pin (Frontiers in Endocrinology, 2023)
Purpose Phthalates are ubiquitous endocrine disruptors that can affect pubertal development in children. The association of fetal and childhood levels of phthalates with pubertal development were explored. Methods We conduct a population-based birth cohort study to investigate the association between prenatal and childhood exposure to phthalates and pubertal development. Initially, a total of 445 children were recruited from 2000 to 2001, of which 90 children were followed for 15 years which measurements of urine and development assessed at 2, 5, 8, 11, and 14 years. We defined higher Tanner stage as the 14-year-old Tanner stage ≥ 4 and 5 for boys and girls, respectively. A logistic regression analysis was conducted to estimate the crude and adjusted odds ratio of a higher Tanner stage at 14 years old. The Pearson correlation coefficient and multiple linear regression were used to estimate the association of testicular volume, uterine volume, ovarian volume, and blood hormones at 14 years of age with the log-transformed concentration of phthalates at 2, 5, 8, 11, and 14 years. Results In boys, a significantly different geometric mean of mono-benzyl phthalate (MBzP) was observed in 11-year-olds; 6.82 and 2.96 in the lower Tanner stage group and higher Tanner stage group. In girls, a significant difference in the geometric mean of mono(2-ethyl-5-hydroxyhexyl) phthalate (MEHHP) in 11-year-olds and mono-ethyl phthalate (MEP) in 2-year-olds was observed; MEHHP was 32.97 and 18.13 in the lower Tanner stage group and higher Tanner stage group, and MEP was 26.54 and 65.74 in the lower Tanner stage group and higher Tanner stage group, respectively. Uterine volume at 14 years old was negatively associated with several phthalate metabolites (MEHP at 8 years old, MnBP at 8 years old, MBzP at 14 years old, MMP prenatally, MMP at 8 years old, and MEP at 8 years old) after adjusting for covariates. However, no significant correlations were found between phthalate metabolites and ovarian or testicular volume. Conclusion Phthalate exposure at certain time points may influence the reproductive development of children during puberty; however, further studies should be conducted to determine the causal nature of this association.